BAHASA MEDSOS SEBAGAI CERMIN IDENTITAS SOSIAL GENERASI Z DI INDONESIA PADA PENGGUNA TIKTOK - Mutiara Basli Ali; Ika Septiana; Senowarsito (STKIP Subang, 2026)
This study examines how language is used on the TikTok platform as a reflection of the social identities of Generation Z members in Indonesia. The language used by TikTok users is not only a means of communication but also serves as a symbol representing group identity, social values, and the shifting cultural dynamics occurring among the younger generation. The method used in this study is a descriptive qualitative method, employing a documentation and discourse analysis approach to various posts, comments, and captions generated by TikTok users aged 16 to 25. The results reveal three main patterns in language use: first, the alternation or mixing of Indonesian and English as a way to demonstrate a cosmopolitan identity; second, the use of slang terms from the community such as “no cap,” “slay,” and “bestie” as signs of warmth and unity within peer groups; and third, the deliberate use of regional languages as a form of expressing ethnic identity and pride in the local environment. These findings suggest that the language choices made by Generation Z on TikTok are deliberate strategies they employ to construct, display, and manage their social identities within the digital environment.